Hunter-gatherer-fishers of the Fish River basin : a contribution to the Holocene prehistory of the eastern Cape - Hall, Simon Lee (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Phil.) -- University of Stellenbosch, 1990.